2002
DOI: 10.1084/jem.20020943
|View full text |Cite
|
Sign up to set email alerts
|

Age at First Viral Infection Determines the Pattern of T Cell–mediated Disease during Reinfection in Adulthood

Abstract: Infants experiencing severe respiratory syncytial virus (RSV) bronchiolitis have an increased frequency of wheeze and asthma in later childhood. Since most severe RSV infections occur between the 8th and 24th postnatal week, we examined whether age at first infection determines the balance of cytokine production and lung pathology during subsequent rechallenge. Primary RSV infection in newborn mice followed the same viral kinetics as in adults but was associated with reduced and delayed IFN-γ responses. To stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
271
3
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(290 citation statements)
references
References 30 publications
15
271
3
1
Order By: Relevance
“…We show that newborn CD4 + T cells are capable of producing comparable levels of IFN‐γ compared to adults but in a delayed fashion compared to adults. The formation of IFN‐γ‐producing cells upon RSV infection in newborn mice is also delayed and may underlie the susceptibility of young infants to severe RSV infections in vivo 3. We propose that RSV‐specific IFN‐γ‐producing memory T cells in adults rapidly produce IFN‐γ In vitro, whereas IFN‐γ production by newborn naïve T cells newborns is delayed.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We show that newborn CD4 + T cells are capable of producing comparable levels of IFN‐γ compared to adults but in a delayed fashion compared to adults. The formation of IFN‐γ‐producing cells upon RSV infection in newborn mice is also delayed and may underlie the susceptibility of young infants to severe RSV infections in vivo 3. We propose that RSV‐specific IFN‐γ‐producing memory T cells in adults rapidly produce IFN‐γ In vitro, whereas IFN‐γ production by newborn naïve T cells newborns is delayed.…”
Section: Discussionmentioning
confidence: 94%
“…The high rate of reinfections by RSV results in a significant burden on health care in infants and elderly 2. Interferon gamma (IFN‐γ) and T cells are essential to mount an adequate immune response during RSV infections in newborn and adult mice 3, 4, 5. This suggests an important role for IFN‐γ in the clearance of primary infections as well as in reinfections 4, 6.…”
Section: Introductionmentioning
confidence: 99%
“…It was recently reported that the timing of respiratory syncytial virus infection during development has distinct effects on subsequent immune responses in mice (26). Indeed, experimental and epidemiological observations lead to the hypothesis that sites of infection, genetic predisposition, and the timing, type, and severity of infections are key factors in determining the development of asthma.…”
Section: Airway-resident Effector Memory Cd8؉ T Cells Can Be Activatementioning
confidence: 99%
“…The genetic interactions between host, virus, and environment that contribute to postbronchiolitic wheeze are likely to be complex (11), which makes it very difficult to uncover the genetic architecture through analysis of human cohorts. We previously developed a murine model to study the delayed consequences of neonatal RSV infection (12). Using this model, we and others have demonstrated that CD8 cells (13), IL-13 (14), IgE (15), and IFN-g (16,17) are all important determinants of disease severity after RSV infection.…”
Section: R Espiratory Syncytial Virus (Rsv) Is the Most Significant Cmentioning
confidence: 99%